Prognostic Impact of Ki-67 Change in Locally Advanced and Early Breast Cancer after Neoadjuvant Chemotherapy: A Single Institution Experience. (4th May 2021) - Pistelli, Mirco; Merloni, Filippo; Crocetti, Sonia; Scortichini, Laura; Tassone, Laura; Cantini, Luca; Agostinelli, Veronica; Bastianelli, Lucia; Savini, Agnese; Berardi, Rossana
Abstract : Systemic neoadjuvant chemotherapy (NCT) is a standard treatment for locally advanced breast cancer (LABC) and for selected early breast cancer (EBC). In these settings, the prognostic and predictive role of Ki-67 before and after NCT is unclear. The aim of our study was to investigate the prognostic role of Ki-67 change in patients not achieving pathological complete response (pCR). We retrospectively analyzed data of patients who did not achieve pCR assessing Ki-67 expression pre- and post-NCT. We stratified three groups: high reduction (>20%), low reduction (1–20%), and no reduction in Ki-67. These groups were correlated with clinical and pathological data by χ 2 test. We estimated disease-free survival (DFS) and overall survival (OS) using Kaplan–Meier method, and we adopted univariate and multivariate Cox proportional hazard models. We selected 82 patients from a database of 143 patients, excluding those who were metastatic at diagnosis, achieved pCR, or lack data regarding Ki-67. Median age at diagnosis was 54 years (range 30–75); 51 patients were Luminal B, 10 human epidermal growth factor receptor 2 (HER-2) enriched, and 21 triple negative. A significant correlation between high Ki-67 reduction and luminal B HER-2-negative subtype was observed (p = 0, 0035 ). The change in Ki-67 was significantly associated with DFS (p = 0, 0596 ) and OS (p = 0, 0120 ), also at multivariate analysis (p = 0, 0256 for DFS; p = 0, 0093 for OS). In particular, as compared to patients with low/no reduction of Ki-67, those with high Ki-67 reduction (>20%) after NCT showed better survival (60% vs. 56% vs. 83% after 5 years from diagnosis, respectively; p = 0.01 ). In conclusion, in our study, Ki-67 change showed a significant prognostic role in breast cancer patients treated with NCT who did not achieve pCR. Crucially, Ki-67 < 20% identifies a high-risk population that may be eligible for clinical trials with novel therapeutic interventions in adjuvant setting.